MORPHOTECTONIC ANALYSIS OF SABAH, EAST MALAYSIA: INFERENCES FROM DIGITAL TERRAIN DATA - Anak Baba, Angelea Leni (Universiti Teknologi PETRONAS, 2015)
Digital Elevation Model (DEM) data, produced from Geographic Information Systems (GIS) expresses topography based on elevation sets. It is a tool to observe and analyse tectonics especially in areas of limited or no access. This project focuses on onshore of Sabah. The main objective of this work is to study the morphotectonics in onshore of Sabah. The study requires one to consider drainage characteristics and the lineaments that make up the area in order to understand the tectonic behavior of the region. Due to inaccessibility of many onshore parts of Sabah, high resolution Digital Elevation Models is used to carry out structural lineament analysis in this study. Manipulation of sun azimuth and sun angles attributes aid in obtaining images with different enhanced features and to observe the continuity of lineaments. The tectonics in Sabah has greatly influenced the drainage system. Based on the stream order analysis, the drainage networks in Sabah are characterized according to Horton-Strahler scheme. Drainage network generated enable watershed basin analysis to be performed by calculating the drainage density of each watershed basin. Tectonic uplift in Sabah is further analysed with the help of Hotspot Analysis. The tectonic interpretation is performed by generating profiles of certain drainage networks in relation to the lineaments and hotspot generated. The results included in this report are lineament mapping, drainage map, watershed basin map, hotspot map and rose diagrams indicating the stress direction in relation to tectonic activities in Sabah. These results will be incorporated in the later phase of the project for a more detailed and thorough analysis and interpretation. Integration of the results is used to study the tectonic evolution that occurred in the area either locally or regionally. By understanding the morphotectonics in a region, tectonic models and basin models can be constructed which would add crucial information for exploration of new prospects.